TEMBANG MACAPAT KINANTHI DAN SINOM CENGKOK MERDI LAMBANG - Darsono Darsono (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
ABSTRACT Macapat is one of the literary works in the Javanese, Sundanese, Balinese and Madurese languages in the form of poetry which is arranged according to certain rules, including guru gatra, guru lagu, andguruwilangan. It has a weighty content. The presentation is through a smooth, gentle, careful and steady cultivation process and always takes into account the elements of ethics and aesthetics. The macapat songswere very popular around the eighteenth century and it can be said to have topped the stairs in the court arts. The macapat songscontain two elements of art, namely literary art and music / sound art which are functioned as a commu-nicative media to convey advice or messages of development. At this time, it is only a historical record of Javanese literature because the macapat songsare now not well known by the heirs. All of this is not due to the influence of the development of science and technology but also due to the lack of teaching infrastructure in the form of books and instructors or less varied existing song material. In connection to this, as a valuable literary work, the macapat songs need to be preserved in order to enrich the cultural treasures of Indonesia. The plans for the creation of macapat songs Kinathi and Sinom with the CengkokMerdiLambang are intended to be a form of participatory action in efforts to preserve and to develop.